Business Model Canvas (BMC) in Developing Micro, Small, Medium Enterprises (MSMES) in Padang City - Trinitaria Marlis Putri; Mayang Larasati; Romy Yunika Putra (Jurnal Multidisiplin Madani, 2022)
Micro, Small and Medium Enterprise (MSMEs) have been through a lot of difficultness while pandemic covid-19 exist. Along with willingness to develop the MSMEs itself and seek for solutions of the problems that were founded, this research used Business Model Canvas (BMC). BMC is an methode using in analyzing a business that looks like a canvas to be painted from which we could see a drawing of the whole aspects of an business, which are; key partners, key activities, key resources, value propositions, customer relationships, channels, customer segments, cost structure, and revenue streams. In this research we use descriptive qualitative analysis with amount of sample population is 40 (fourty) MMSEs that spread in several districts in Padang City. Result showed that the main problem of the MMSEs is they didn’t have a cash book, didn’t digitalize their business, and still need funding to recover their business after the long pandemic. For the next research, we suggest, to discuss about digitalization of micro and small business so that they will have an significant growth in sales, profit, and run their business effectively and MSMEs to learn making a simple financial record of their own